Caenorhabditis elegans as a model system to evaluate neuroprotective potential of nano formulations - Chauhan, Payal; Wadhwa, Karan; Singh, Govind (Frontiers in Nanotechnology, 2022)
The impact of neurodegenerative illnesses on society is significant, but the mechanisms leading to neuronal malfunction and death in these conditions remain largely unknown despite identifying essential disease genes. To pinpoint the mechanisms behind the pathophysiology of neurodegenerative diseases, several researchers have turned to nematode C. elegans instead of using mammals. Since C. elegans is transparent, free-living, and amenable to culture, it has several benefits. As a result, all the neurons in C. elegans can be easily identified, and their connections are understood. Human proteins linked to Neurodegeneration can be made to express in them. It is also possible to analyze how C. elegans orthologs of the genes responsible for human neurodegenerative diseases function. In this article, we focused at some of the most important C. elegans neurodegeneration models that accurately represent many elements of human neurodegenerative illness. It has been observed that studies using the adaptable C. elegans have helped us in better understanding of human diseases. These studies have used it to replicate several aspects of human neurodegeneration. A nanotech approach involves engineering materials or equipments interacting with biological systems at the molecular level to trigger physiological responses by increasing stimulation, responding, and interacting with target sites while minimizing side effects, thus revolutionizing the treatment and diagnosis of neurodegenerative diseases. Nanotechnologies are being used to treat neurological disorders and deliver nanoscale drugs. This review explores the current and future uses of these nanotechnologies as innovative therapeutic modalities in treatment of neurodegenerative diseases using C elegans as an experimental model.